2020
DOI: 10.3390/biom10091350
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Roles for the INK4a/ARF (CDKN2A) Locus in Adipose Tissue: Implications for Obesity and Type 2 Diabetes

Abstract: Besides its role as a cell cycle and proliferation regulator, the INK4a/ARF (CDKN2A) locus and its associated pathways are thought to play additional functions in the control of energy homeostasis. Genome-wide association studies in humans and rodents have revealed that single nucleotide polymorphisms in this locus are risk factors for obesity and related metabolic diseases including cardiovascular complications and type-2 diabetes (T2D). Recent studies showed that both p16INK4a-CDK4-E2F1/pRB and p19ARF-P53 (p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 113 publications
0
21
0
Order By: Relevance
“…Knockdown of p16INK4A enhanced adipogenesis in vitro, and adipose tissue formation especially in the pericardial fat was enhanced in p16INK4A knockout mice [ 208 ]. The role of p16INK4A in adipogenesis seems to be related via several molecular mechanisms to PPAR gamma (reviewed in [ 214 ]). Senolytic drug treatment or the use of INK-ATACC mice has been shown to alleviate metabolic and adipose tissue dysfunction, improve glucose tolerance, enhance insulin sensitivity, lower circulating inflammatory mediators, and promote adipogenesis in obese mice [ 239 ].…”
Section: P16ink4a P14arf/p19arf and P21 In Homeostasismentioning
confidence: 99%
See 1 more Smart Citation
“…Knockdown of p16INK4A enhanced adipogenesis in vitro, and adipose tissue formation especially in the pericardial fat was enhanced in p16INK4A knockout mice [ 208 ]. The role of p16INK4A in adipogenesis seems to be related via several molecular mechanisms to PPAR gamma (reviewed in [ 214 ]). Senolytic drug treatment or the use of INK-ATACC mice has been shown to alleviate metabolic and adipose tissue dysfunction, improve glucose tolerance, enhance insulin sensitivity, lower circulating inflammatory mediators, and promote adipogenesis in obese mice [ 239 ].…”
Section: P16ink4a P14arf/p19arf and P21 In Homeostasismentioning
confidence: 99%
“…Bone marrow-derived macrophages from p16INK4A knockout mice show polarization towards an anti-inflammatory M2 phenotype and silencing of p16INK4A in macrophages from obese patients equally shifts the phenotype towards M2 macrophages [ 227 , 228 ]. These effects seem to be independent of proliferation and senescence [ 214 ], although earlier data indicated a critical role of the p16INK4A locus in proliferation and programming of progenitor cell populations [ 243 ]. Besides the effects of p16INK4A on macrophage polarization in adipose tissue, also increased white-to-brown adipocyte conversion associated with enhanced energy expenditure and insulin sensitivity has been reported in p16INK4A knockout mice [ 215 ].…”
Section: P16ink4a P14arf/p19arf and P21 In Homeostasismentioning
confidence: 99%
“…p16 INK4a seems to inhibit adipogenesis while knock-down of p16 INK4a in 3T3-L1 mouse preadipocytes increased adipogenesis [111]. Additionally, it has been speculated that increased p16 INK4a levels during ageing and obesity might contribute to the recruitment of macrophages in adipose tissue as well as the prevention of macrophage M2 polarisation with an increased risk of developing type two diabetes [113]. Thus, p16 INK4a seems to be a key factor that is implicated in adipose tissue during ageing as well as obesity.…”
Section: P16 Ink4a and Adipocyte Senescencementioning
confidence: 99%
“…This mechanism is repressed through the activation of CDK inhibitors, namely p16 INK4A , that bind to CDK and avoid cyclinD/CDK4 complex formation, and subsequently repress pRb phosphorylation and E2F1 transcriptional activity (25). Although these mechanisms mainly control the progression of the cell cycle (26), recent studies have reported important roles for the E2F1-pRb-CDK4 pathway beyond the sole regulation of cell proliferation (27,28). Indeed, several reports have demonstrated the role of the E2F1 pathway in the control of metabolic functions in non-proliferative cells, including adipocytes (29,30), hepatocytes (31)(32)(33), muscle and brown adipose tissue (34,35) and pancreatic b cells (17)(18)(19)36).…”
Section: Introductionmentioning
confidence: 99%